William of Saint-Thierry on the Holy Spirit's Personal Identity - Hastings, Elizabeth (Cistercian studies quarterly, 2002)
Focuses on the interpretation of William of Saint-Thierry on the personal identity of Holy Spirit in terms of the Augustinian understanding. Relationship between the human soul and the person of the Spirit; Conclusions on the uniqueness of person; Assistance to the contemporary dilemma of Western Christian spirituality.